Roles of Commensal Microbiota in Pancreas Homeostasis and Pancreatic Pathologies - Camila Leal-Lopes; Fernando J. Velloso; Julia C. Campopiano; Mari C. Sogayar; Ricardo G. Correa (Journal of Diabetes Research)
The pancreas plays a central role in metabolism, allowing ingested food to be converted and used as fuel by the cells throughout the body. On the other hand, the pancreas may be affected by devastating diseases, such as pancreatitis, pancreatic adenocarcinoma (PAC), and diabetes mellitus (DM), which generally results in a wide metabolic imbalance. The causes for the development and progression of these diseases are still controversial; therefore it is essential to better understand the underlying mechanisms which compromise the pancreatic homeostasis. The interest in the study of the commensal microbiome increased extensively in recent years, when many discoveries have illustrated its central role in both human physiology and maintenance of homeostasis. Further understanding of the involvement of the microbiome during the development of pathological conditions is critical for the improvement of new diagnostic and therapeutic approaches. In the present review, we discuss recent findings on the behavior and functions played by the microbiota in major pancreatic diseases and provide further insights into its potential roles in the maintenance of pancreatic steady-state activities.